SUBMERGED GEOMORPHOSITES IN THE MARINE PROTECTED AREAS OF SARDINIA (ITALY): ASSESSMENT AND IMPROVEMENT - Orrù, Paolo; Panizza, Valeria; Ulzega, Antonio (Alpine and Mediterranean Quaternary, 2005)
P. Orrù et al., Submerged Geomorphosites in the marine protected areas of Sardinia (Italy): assessment and improvement. (IT ISSN 0394-3356, 2005). Inside the studies conducted around the theme of the improvement of the Italian geological and geomorphological heritage, studies undertaken in the ambit of different research projects and working groups, we want, with this work, to experiment and to verify the applicability of the methodologies of assessment and census of the sites of geological and geomorphological interest in submerged areas. This with the aim to gather the most greater number of possible data on the characteristics of the physical submerged resources in protected sea areas, both for scientific purpose and for a possible fruition by the public of the scuba divers. Further intent is, in fact, that to drive the "tourist" toward a more aware and global knowledge and perception of the underwater world, in all the aspects of any cultural interest, and not only for those aspects tied up to the complex of the living organisms. The experimentation of the methodology and the study on two protected sea areas of the island of Sardinia (Italy) is proposed: the protected sea area of C. Carbonara and the protected sea area of C. Caccia.